Semiotic Analysis of Phishing Mode Prevention Efforts Implemented through BCA Advertisements “Don’t Know? Kasih No!” - Ichsan, Lulu Afifah (Gorga : Jurnal Seni Rupa, 2025)
The rise of phishing crimes targeting all levels of society necessitates effective public education. BCA’s advertisement "Don't Know? Kasih No!" serves as an educational campaign designed to raise awareness about the dangers of phishing, particularly regarding suspicious requests for personal information. Based on Ferdinand de Saussure’s semiotic theory, the advertisement is analyzed through the relationship between the signifier—such as visual and verbal elements—and the signified, or the meanings perceived by the audience regarding cyber threats. The three-act structure—introduction, conflict, and resolution—creates a cohesive and easily comprehensible narrative. The visualization of characters and everyday situations strengthens the message, while the slogan “Don't Know? Kasih No!” acts as a memorable reinforcement. This strategy proves effective in delivering a profound message in a concise and engaging manner, while also encouraging behavioral change. The semiotic approach in the "Don't Know? Kasih No!" advertisement significantly enhances the effectiveness of educational messaging about phishing prevention by leveraging the connection between signs and the audience's everyday experiences.